Recent advances in apoptosis, mitochondria and drug resistance in cancer cells - Indran, I.; Tufo, G.; Pervaiz, Shazib; Brenner, C. (Elsevier, 2011)
Defective or inefficient apoptosis is an acquired hallmark of cancer cells. Thus, a thorough understanding of apoptotic signaling pathways and insights into apoptosis resistance mechanisms are imperative to unravel novel drug targets for the design of more effective and target selective therapeutic strategies. This review aims at providing an overview of the recent understanding of apoptotic signaling pathways, the main mechanisms by which cancer cells resist apoptotic insults, and discusses some recent attempts to target the mitochondrion for restoring efficient cell death signaling in cancer cells. This article is part of a Special Issue entitled: Bioenergetics of Cancer. © 2011 Published by Elsevier B.V.